Impact of Corporate Governance Reform on the Management Effectiveness of State Owned Enterprises in Lithuania in 2012–2014 - Jurkonis, Liudas; Merkliopas, Šarūnas; Kyga, Karolis (Ekonomika, 2016)
Following previous research on the management efficiency of the state-owned enterprises (SOEs) in Lithuania, this paper extends the discussion via analysis of the broader period of time not only focusing on 1 year caption (2012), but trying to identify the impacts (if any) of the corporate governance reform of the SOEs in Lithuania looking at the data of 2012–2014. To ensure the consistency and comparability of the results, the theoretical background is sought to be maintained as similar as in the previous papers, following the paradigms of (post) new public management, principle-agent theory, corporate governance guidelines established by such international organisations as the Organisation for Economic Co-operation and Development (OECD), the World Bank, the International Monetary fund and others. In addition to the quantitative part of the analysis (quantitative analysis of the relationship between management of SOEs and results of its operations as measured by Return on Equity (ROE)), case studies representing biggest Lithuanian SOEs and – accordingly – 3 main sectors Lithuanian SOEs are acting in are analysed to understand if and what (i) actual changes of the corporate governance principles are impacting the management effectiveness of SOEs, as well as (ii) what are the limiting factors (if any) reducing the positive effects of the changes being introduced with the new reform. For both parts of the analysis (quantitative and case studies) we focus on (i) the main elements of corporate governance being introduced by the SOE reform and (ii) the relations of the SOEs and the shareholder of theirs (Government and the society). By applying the above described approach, the paper seeks to (i) understand not only the effects of corporate governance on management and performance of SOEs per se, but also include the time dimension with the purpose to understand (confirm) if previous findings (e.g., the fact that board independence and transparency were the key factors influencing SOEs management efficiency in 2012) are sufficiently sustainable outcomes of the reform, which would still be valid in the 3 year period (2012-2014), as well as (ii) explain the most relevant (in terms of impact on management effectiveness) corporate governance principles that should be applied or be promoted stronger in Lithuanian SOEs.